Septic shock following operative hysteroscopy in a menopausal woman: A case report and review of the literature - Moad Belouad; Abdelhamid Benlghazi; Lina Belkouchi; Yassine Bouhtouri; Saad Benali; Jaouad Kouach (Wolters Kluwer Medknow Publications, 2023)
Minimally invasive gynecologic surgery such as hysteroscopy has a low risk of complications. Infections, however, are more common in the presence of risk factors such as smoking, history of pelvic inflammatory disease, and endometriosis. We report the case of a patient who underwent operative hysteroscopy without immediate complications and was admitted 2 days later to the emergency department in a severe state of septic shock. With multiple organ failures requiring admission to an intensive care unit, the patient died despite extensive antibiotic therapy and vasoactive drugs. Ascending infection can be a potentially fatal complication of hysteroscopy, even in the absence of known risk factors.